Tanner v. Oregon Health Sciences University: Justifying the Mandate for Domestic Partner Benefits - Chusid, Jodie Leith (Columbia Journal of Gender and Law, 1999)
On August 8, 1996, Multnomah County Circuit Judge Stephen Gallagher handed down a first-of-its-kind order. Unlike other cases involving domestic partner benefits which focus on marital status discrimination, the Oregon case is premised on sex discrimination. In Tanner v. Oregon Health Sciences University, Judge Gallagher ordered the state of Oregon to offer group life, medical, and dental insurance benefits to the domestic partners of homosexual state employees. Judge Gallagher held that the state’s current fringe benefit plan violates Article I, section 20 of the Oregon Constitution and Oregon Revised Statute (ORS) § 659.030(1)(b), which prohibit sex discrimination in employment. The decision enjoined the State of Oregon, Oregon Health Sciences University (OHSU), the State Board of Higher Education, and the State of Oregon’s State Employee’s Benefits Board (SEBB) from denying group life and group medical and dental insurance coverage to the domestic partners of homosexual employees when such employment-related benefits are afforded to the spouses of its heterosexual employees. The Tanner opinion is problematic because it is void of legal analysis- statutory, constitutional, common law, or otherwise-to justify the outcome. Instead, Judge Gallagher’s opinion is premised upon the social injustices that continue to afflict the gay and lesbian communities; as a result, the decision is ripe for appeal. On August 30, 1997, the Oregon Attorney General’s office announced its decision to appeal the case. At the very least, the appeal is perfunctory, intended to force the Court of Appeals to set binding precedent. On the other hand, the Attorney General’s challenge could be a genuine effort to prove that the state’s policies and practices are both non- discriminatory and constitutional. In either scenario, it is speculated that this case will reach the Oregon Supreme Court, with the possibility of becoming binding law in Oregon. Both the Court of Appeals and the Supreme Court decisions are heavily anticipated because the implications could be far- reaching. Depending on the courts’ analyses, homosexuals may be deemed a protected class in Oregon. Such a ruling would alter the current face of many of the state’s legal doctrines and pave the way for a potentially successful challenge to the state’s prohibition on same-sex marriages. This Comment first examines the Tanner case: the claim, the issues, the arguments set forth by both parties, and the holding. Next, the available constitutional, legal, and social arguments will be presented and analyzed applying the Tanner facts. Finally, this Comment concludes that the circuit court holding in Tanner v. OHSU can withstand constitutional and legal scrutiny, thereby taking Oregon a step closer to deeming homosexuals a protected class under the state’s employment non-discrimination law and the Oregon Constitution.